Influencing factors on safety culture in mining industry: A systematic literature review approach - Siti Noraishah, Ismail; Azizan, Ramli; Hanida, Abdul Aziz (Elsevier, 2021)
Safety culture is a promising solution to reduce mining accidents. However, the systematic review on influencing factors of safety culture in the mining industry is still lacking. The objective of the study is to investigate the influencing factors of safety culture in the mining industry. A systematic literature review (SLR) study by applying the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) review method has identified 33 articles on safety culture in mining from twelve countries: China, USA, India, Sweden, Brazil, Turkey, Kenya, South Africa, Mongolia, Russia, Taiwan, and Ghana. Qualitative studies used four main data-bases, such as Science Direct, Scopus, Web of Science and SpringerLink databases. Three main themes have been developed; psychological, situational, and behavioural dimensions and produced 17 sub-themes. The study found that the behavioural dimension has the greatest influencing factor in constructing a positive safety culture (47%), followed by the situational dimension (29%) and psychological dimension (24%). Moreover, the management’s commitment was the biggest contributor in constructing safety culture in the mining industry. In conclusion, a systematic review study could hopefully increase awareness among mine owners, miners, government, and policymakers in providing better understanding on safety culture to reduce mining accidents in the future.